Two new species of Potentilla (Rosaceae) from central Mexico - Rzedowski, Jerzy; Calderón De Rzedowski, Graciela (Instituto de Ecología, A.C., 2005)
Potentilla butandae and P. queretarensis are described as new and illustrated. The first one is known from a restricted area of northeastern Guanajuato and is related to P. ranunculoides Humb. & Bonpl. ex Nestler, P. rydbergiana Rose and P. subcoriacea Rydb. The second was collected only once in the municipality of San Joaquín of the state Querétaro and seems to be related to P. goldmanii Painter.